Occupational Therapy in an Intensive Care Unit (Icu): Experience Report on Work with Caregivers/Family Members in a Public Hospital - Acevedo-Perez, F (CUBA EDITORA, 2024)
There is little Latin American literature regarding the practices of occupational therapists in the context of intensive care units. Although it is clear which interventions are mostly carried out, the details of these are not evident, especially the description of the work carried out with caregivers/family members. For this reason, the objective of the article is to describe this process based on one hand, on a committed and therapeutic bond to understand each subject/family in its uniqueness and on the other, on education from the recognition of the diversity of people s knowledge. Therefore, this article reports an experience of what happens in a public hospital in Chile, where there has been work in the discipline for approximately 10 years, considering the particular actions that are carried out jointly with caregivers/family members, highlighting the following two strategies 1) Committed and therapeutic accompaniment initiated from the initial semistructured interview as the first meeting between the occupational therapist and caregivers/family members, and 2) Education as a strategy and space for generating support and explicit mutual knowledge at three specific moments in the process. It is concluded that caregivers/family members are fundamental figures during care in an intensive care unit and it is necessary to reflect on the singularities that exist during the course of the intervention, recognizing their knowledge and stories.
Keywords: Occupational Therapy; Intensive Care Units; Caregivers; Family; Rehabilitation